2023
DOI: 10.1371/journal.pone.0282856
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and analysis of literature on the organisation of eight European academic medical centres—A scoping review

Abstract: Academic Medical Centres (AMCs) are important organisations for shaping healthcare. The purpose of this scoping review is to understand the scope and type of evidence related to the organisation of European AMCs. We selected the study population intending to obtain a demographic cross-section of European countries: Czech Republic, Germany, Latvia, the Netherlands, Poland, Spain, Sweden and the UK. We focused our search strategy on the relationship between medical schools and AMCs, the organisation of governing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Knowledge about the current research topic is still in its infancy. It has been found that there is still little scientific literature available on the governance of academic medical centres ( 55 ). At the same time, it is known that the governance problems of European AMCs are perceived as similar ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the current research topic is still in its infancy. It has been found that there is still little scientific literature available on the governance of academic medical centres ( 55 ). At the same time, it is known that the governance problems of European AMCs are perceived as similar ( 56 ).…”
Section: Discussionmentioning
confidence: 99%